A influência do convívio intergeracional no cuidado ao idoso com demência - Santos, Bruna Rodrigues dos (Universidade Federal de São Carlos, 2017)
Studies show that caregivers of elderly people with dementia present high levels of stress and overload, as well as difficulties in coping with situations related to care. The hypothesis of this research is that the conviviality with the elderly during childhood brings positive experiences to the caregiver as an adult. The main objective of this study is to compare the overload, perceived stress and coping of caregivers of elderly people diagnosed with some type of dementia who lived and did not live with the elderly during their childhood. It is a cross-sectional, descriptive and comparative quantitative study. The research was conducted with informal caregivers of elderly people with dementia (n=102) enrolled in an outpatient clinic of a Brazilian federal university. The instruments used to collect data were: characterization questionnaire, Coping Strategies Inventory, Zarit Burden Scale and Perceived Stress Scale. Data were analyzed through descriptive, correlational and comparative statistics. Evaluations were previously scheduled and performed at the caregiver's home. All ethical care was respected and the research was approved by the Research Ethics Committee of the Federal University of São Carlos. The results showed that: 1- Most informal caregivers of elderly people with dementia are women, married, with a mean age of 57,1 (±3.9) years. 2- Regarding aspects of care, the majority take care of the parents, reside in the same household as the elderly and are primary caregivers. 3 - The score obtained in the Coping Strategies Inventory presented a strong relation and inversely proportional to the score obtained in the Zarit Burden Scale (rho=-0,747, p<0.01) and with the score obtained in the Perceived Stress Scale (rho=-0,850, p<0.01). 4- The group of caregivers of elderly people with dementia who lived with the elderly during childhood presented better coping, less stress and less overload than the group of informal caregivers of elderly people with dementia who did not live with the elderly in childhood, with differences Statistically significant. Therefore, for this sample of participants, living with the elderly in childhood had a positive influence on the experience of caring for an elderly relative in the future, confirming the hypothesis study.
Keywords: Cuidadores; Idoso; Demência; Caregivers; Aged; Dementia; CIENCIAS DA SAUDE::ENFERMAGEM